Crayfish plague in Czechia: Outbreaks from novel sources and testing for chronic infections - Mojžišová, Michaela; Mrugała, Agata; Kozubíková-Balcarová, Eva; Vlach, Pavel; Svobodová, Jitka; Kouba, Antonín; Petrusek, Adam (Journal of invertebrate pathology, 2020)
The crayfish plague pathogen Aphanomyces astaci, which is among the most studied pathogens of aquatic invertebrates, co-evolved with North American crayfish species but threatens crayfish on other continents. The pathogen causes mass mortalities, particularly in Europe. In this study we document 12 crayfish plague outbreaks that occurred from 2014 to 2019 in Czechia and, by using available molecular techniques (microsatellite and mtDNA markers), we reveal the A. astaci genotypes involved. Our results provide the first evidence of strains from genotype group D, originally associated with the host Procambarus clarkii, causing Astacus astacus and Austropotamobius torrentium mass mortalities in Czechia. Moreover, mtDNA sequencing confirmed two distinct haplotypes of the D haplogroup, indicating two independent sources of infection, presumably originating from ornamental crayfish in the pet trade or spreading from crayfish established in neighbouring countries. Genotype group A was recorded in two As. astacus mortalities, and genotype group E, associated with Faxonius limosus, in two Au. torrentium and three As. astacus mortalities. Microsatellite genotyping also reidentified the unusual genotype SSR-Up in two As. astacus outbreaks, ten years after its first documented occurrence. In addition, we tested healthy-appearing indigenous crayfish from 25 localities for potential chronic infections. No traces of A. astaci DNA were detected; chronic infections in European crayfish species thus do not seem a pervasive phenomenon in Czechia. However, their role as A. astaci latent reservoirs, especially in Pontastacus leptodactylus populations introduced to the country since the late 19th century, cannot be excluded.
Keywords: Astacoidea; Genotype groups; Animals; Invasive crayfish distribution; Česká republika; Mass mortalities; Mitochondrial haplogroups; Genotype; zvířata; genotyp; Microsatellite genotyping; Czech Republic; severní raci; Aphanomyces astaci; Aphanomyces